Studying Problem Solving through Group Discussion in Chat Rooms - Inna Kozlova (Scripta Manent)
In the present article we use a chat conversations’ corpus to study the process of resolving language problems. Our corpus includes chat conversations which took place between LSP students engaged in correcting errors in their peers’ summaries. The participants worked in groups and used the Windows Messenger program for communication within the group. Their task also included making use of electronic dictionaries and other reference materials. The conversations’ corpus obtained as a result of this exercise was analyzed holistically for possible indicators of each particular stage of the problem solving process. Later these indicators were validated throughout the entire corpus. Each problem solving process was thus represented as a chain of indicators and acceptability was determined for each error correction. The resulting problem solving chains were used to prove our hypotheses concerning internal and external support in text reproduction.